Comprehensive analysis of single-repeat R3 MYB proteins in epidermal cell patterning and their transcriptional regulation in Arabidopsis - Wang, Shucai (BioMed Central, 2008)
BACKGROUND: Single-repeat R3 MYB transcription factors are critical components of the lateral inhibition machinery that mediates epidermal cell patterning in plants. Sequence analysis of the Arabidopsis genome using the BLAST program reveals that there are a total of six genes, including TRIPTYCHON (TRY), CAPRICE (CPC), TRICHOMELESS1 (TCL1), and ENHANCER of TRY and CPC 1, 2, and 3 (ETC1, ETC2 and ETC3) encoding single-repeat R3 MYB transcription factors that are approximately 50% identical to one another at the amino acid level. Previous studies indicate that these single-repeat R3 MYBs regulate epidermal cell patterning. However, each of the previous studies of these single-repeat R3 MYBs has been limited to an analysis of only a subset of these six genes, and furthermore, they have limited their attention to epidermal development in only one or two of the organs. In addition, the transcriptional regulation of these single-repeat R3 MYB genes remains largely unknown. RESULTS: By analyzing multiple mutant lines, we report here that TCL1 functions redundantly with other single-repeat R3 MYB transcription factors to control both leaf trichome and root hair formation. On the other hand, ETC1 and ETC3 participate in controlling trichome formation on inflorescence stems and pedicles. Further, we discovered that single-repeat R3 MYBs suppress trichome formation on cotyledons and siliques, organs that normally do not bear any trichomes. By using Arabidopsis protoplast transfection assays, we found that all single-repeat R3 MYBs examined interact with GL3, and that GL1 or WER and GL3 or EGL3 are required and sufficient to activate the transcription of TRY, CPC, ETC1 and ETC3, but not TCL1 and ETC2. Furthermore, only ETC1's transcription was greatly reduced in the gl3 egl3 double mutants. CONCLUSION: Our comprehensive analysis enables us to draw broader conclusions about the role of single-repeat R3 MYB gene family than were possible in the earlier studies, and reveals the genetic basis of organ-specific control of trichome formation. Our findings imply the presence of multiple mechanisms regulating the transcription of single-repeat R3 MYB genes, and provide new insight into the lateral inhibition mechanism that mediates epidermal cell patterning.